Pemberdayaan Masyarakat Berbasis Gerakan Literasi di Taman Baca Masyarakat Karya Mulya di Kecamatan Sematang Borang Kota Palembang - Eni Murdiati; Muzaiyanah Muzaiyanah; Alma Nisya (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This research is entitled community empowerment based on literacy movements at the Karya Mulya Community Reading Park in Sematang Borang District, Palembang City. Community empowerment is an effort to develop community independence and welfare and improve attitudes, skills, behavior, abilities, awareness and utilize resources. Empowerment does not only talk about economic material aspects, but other aspects that can support empowerment, one of which is by providing encouragement to the community to be independent and empowered, active and creative in welcoming collective independence, namely with the existence of a literacy movement initiated by community groups in the form of reading parks. Community is a real form of empowerment. The aim of this research is to determine the community empowerment process that has been carried out by the Karya Mulya community reading park through the literacy movement, as well as the obstacles that occur during the empowerment process. Researchers use a qualitative research approach through direct observation in the field. Through observation, interviews and documentation methods, the author gathered information from the Founder of the Karya Mulya Community Reading Park, the Manager and Volunteers of the Karya Mulya Community Reading Park and the community around the Community Reading Park. The results of this research show that the Karya Mulya Community Reading Park has carried out several community empowerment programs and activities, including community empowerment through the overall literacy movement with mobile library activities, language months, book reviews, work degrees, and reading degrees. The obstacles faced during community empowerment activities carried out by the Karya Mulya community reading park are funding, facilities and infrastructure, and volunteers.